Situation looks good for BN to call the polls now - Dr M - Borneo Post, (KK) (The Borneo Post, 2012)
SINTOK : Former prime minister Tun Dr Mahathir Mohamad said yesterday said yesterday he feels that 13th general will be held soon as the situation "looks good" for the ruling coalition.